HUBUNGAN ANTARA PERBANDINGAN SOSIAL DAN KEPUASAN HIDUP PADA REMAJA - Nopiati Arifin; Basti Basti; Faradillah Firdaus (CV. ADIBA AISHA AMIRA, 2022)
Adolescence often do social comparisons with other individuals in their development process. Social comparison will make adolescents feel dissatisfied with the life they are experiencing at the time. This study aimed to determine whether there is a relationship between social comparison and life satisfaction in adolescence. The subjects of this study were 251 adolescents. The sampling technique used in this study is accidental sampling. The measuring instrument used is the social comparison scale and life satisfaction scale. This study used Rank Spearman correlation analysis techniques. The results showed that there was a negative relationship between social comparison and life satisfaction in adolescence (r= -0,196, p=0,002), This study illustrates that the higher level of social comparison, the lower tendency of life satisfaction in adolescents.